The effect of volatilisation of refractory metal oxides on the cyclic oxidation of Ni-base superalloys - Brewster, Gyaneshwara; Edmonds, I. M.; Gray, Simon (Springer Science Business Media, 2014)
The role of refractory metals on the bare oxidation behaviour of a range of compositionally complex single crystal Ni-base superalloys has been investigated using a range of techniques. It has been shown that this series of fourth generation alloys were borderline alumina formers at 1,100 °C, and their cyclic oxidation performance was detrimentally affected by increased levels of Mo and Co. In addition, there was strong evidence that Re, Ru and Mo were lost through the process of cyclic oxidation, which supports the hypothesis that these elemental additions were lost through volatilisation/sublimation, contributing to their poor cyclic oxidation performance.